Green Price and Green Place: How Important is Green Consumer Knowledge for Purchasing Sustainable Products? - Erlan Herdiatna; Agus Setyo Pranowo; Yuary Farradia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the role of green consumer knowledge in mediating the influence of green price and green place on the purchasing decisions of environmentally friendly AMDK Aqua Life products in Bogor City. This study uses a quantitative approach with a survey method involving 200 respondents who are Aqua Life consumers. Data analysis was conducted using Structural Equation Modeling (SEM) with the help of LISREL 8.80 software. The research results show that green price has a positive and significant effect on green consumer knowledge, while green place does not have a significant effect. Green price has a negative and significant effect on purchasing decisions, while green place has a positive and significant effect. In addition, green consumer knowledge has been proven to have a positive and significant impact on purchasing decisions. The mediation test using the Sobel test shows that green consumer knowledge can mediate the influence of green price on purchasing decisions, but does not mediate the influence of green place. These findings affirm that green consumer knowledge plays an important role in raising environmental awareness and encouraging the purchase of eco-friendly products. Therefore, improving consumer literacy and effective distribution strategies are key to strengthening sustainable consumption behavior.